Pengaruh Employer Branding dan E-recruitment terhadap Minat Generasi Z untuk Melamar Pekerjaan di Perusahaan Retail (Studi Pada Perusahaan Retail di Kota Malang) - Awanji, Muhammad Rif’an; Mawardi, Muhammad Cholid; Utama, Satria Putra (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This study aims to determine the influence of employer branding and e-recruitment on Generation Z's interest in applying for jobs at retail companies in Malang City. The research is motivated by the rise of digital strategies in the recruitment process and the importance of employer branding in attracting job seekers, particularly from Generation Z.This research uses a quantitative approach with a survey method by distributing questionnaires to 100 respondents, consisting of active students and recent graduates in Malang. The analysis technique employed is multiple linear regression using SPSS software.The results of the study show that both employer branding and e-recruitment have a positive and significant effect on Generation Z's job application interest. Partially, e-recruitment has a more dominant influence than employer branding. These findings indicate that effective digital recruitment processes and a strong employer image can increase Generation Z's interest in applying for jobs at retail companies. Keywords : Employer Branding, E-Recruitment, Job Application Interest, Generation Z, Retail Company